Here comes destructosaurus! ebook - Reynolds, Aaron (2014)
Watch the unstoppable destructive force of a raging temper tantrum! Tremble at the enormous mess and disrespectful roaring! Despair as no amount of scolding can stem the heedless fury! Someone is heading for a time-out, Mister! Anyone who has witnessed (or been) a toddler in the throes of a full-blown fit will delight in this clever book's moviemonster rampage, and may just come away from it with a bit more sympathy for toddler and caregiver. Plus, this is the fixed format version, which will look almost identical to the print version. Additionally for devices that support audio, this ebook includes a read-along setting.